Adjuvant therapy following oesophagectomy for adenocarcinoma in patients with a positive resection margin. Issue 13 (29th September 2020) - Bott, R K; Beckmann, K; Zylstra, J; Wilkinson, M J; Knight, W R C; Baker, C R; Kelly, M; Maisey, N; Qureshi, A; Sevitt, T; Van Hemelrijck, M; Smyth, E C; et al.
Abstract: Background: The role of adjuvant therapy in patients with oesophagogastric adenocarcinoma treated by neoadjuvant chemotherapy is contentious. In UK practice, surgical resection margin status is often used to classify patients for receiving adjuvant treatment. The aim of this study was to assess the survival benefit of adjuvant therapy in patients with positive (R1) resection margins. Methods: Two prospectively collected UK institutional databases were combined to identify eligible patients. Adjusted Cox regression analyses were used to compare overall and recurrence-free survival according to adjuvant treatment. Recurrence patterns were assessed as a secondary outcome. Propensity score-matched analysis was also performed. Results: Of 616 patients included in the combined database, 242 patients who had an R1 resection were included in the study. Of these, 112 patients (46·3 per cent) received adjuvant chemoradiotherapy, 46 (19·0 per cent) were treated with adjuvant chemotherapy and 84 (34·7 per cent) had no adjuvant treatment. In adjusted analysis, adjuvant chemoradiotherapy improved recurrence-free survival (hazard ratio (HR) 0·59, 95 per cent c.i. 0·38 to 0·94; P =  0·026), with a benefit in terms of both local (HR 0·48, 0·24 to 0·99; P =  0·047) and systemic (HR 0·56, 0·33 to 0·94; P =  0·027) recurrence. In analyses stratified by tumour response to neoadjuvant chemotherapy, non-responders (Mandard tumour regression grade 4–5) treated with adjuvant chemoradiotherapy had an overall survival benefit (HR 0·61, 0·38 to 0·97; P =  0·037). In propensity score-matched analysis, an overall survival benefit (HR 0·62, 0·39 to 0·98; P =  0·042) and recurrence-free survival benefit (HR 0·51, 0·30 to 0·87; P =  0·004) were observed for adjuvant chemoradiotherapy versus no adjuvant treatment. Conclusion: Adjuvant therapy may improve overall survival and recurrence-free survival after margin-positive resection. This pattern seems most pronounced with adjuvant chemoradiotherapy in non-responders to neoadjuvant chemotherapy. Graphical Abstract: In UK practice, surgical resection margin status is often used to stratify patients for receipt of adjuvant treatment. This cohort study suggested both an overall and recurrence-free survival benefit following adjuvant therapy in patients with positive margins, who had undergone neoadjuvant chemotherapy and resectional surgery for oesophageal adenocarcinoma. The benefit seemed greater with adjuvant chemoradiotherapy and in poor responders to neoadjuvant chemotherapy. Decreases recurrence and improves survival